The Effect of Al Particles Size on the Thermal Behavior and Kinetics of Al-MnO2 Thermite System - Jia-xing Song; Tao Guo; Wen Ding; Miao Yao; Li Yang; Xiao-nan Zhang; Zhong-shen Yu; Jia-xiang Wu; Jun Zhang; Xiang Fang (Advances in Materials Science and Engineering)
Micron-MnO2 powder has unique thermal decomposition process compared with other metal oxides, and the different characteristics of components in thermite could affect the thermal performance of the whole system directly. In this work, the Al powder with different three particle sizes was combined with micron-MnO2 to prepare the Al-MnO2 thermite system, and the effect of Al powder particle sizes on the whole thermal behavior was studied. Firstly, the thermal decomposition process of micron-MnO2 and purity of Al powder are tested by TG-DSC. By using ultrasonic dispersion method, the fuel-rich thermite samples were prepared and characterized by SEM and TG-DSC at different heating rates. The Kissinger method was also employed to calculate the activation energy for the first exothermic peak. It was found that the thermal decomposition process of MnO2 in the thermite system can be significantly disturbed by different Al particles size. In other words, the effect of Al particle sizes on the thermite can be magnified due to the unique decomposition properties of micron-MnO2 instead of onset temperature of exothermic reaction changing simply. The activation energy of thermite system decreased with the reduction of Al particle sizes in micron-level, while in nanolevel the activation energy markedly increased. Finally, the possible reasons for phenomenon were discussed.